The great man-made river project : Water the source of life = Le projet de la grande riviera artificielle (Tripoli, Libya)
The Great Man-Made River Authority was established in 1983 to implement the greatest feat of civil engineering ever undertaken by mankind. "The Libyan arab people through their revolutionary free will have chosen to build this great man made river".
The Vision; Construction; Operation; Usage; Maintenance; The Future; Facts & Figures; Infrastructure
Interactive multimedia presentation in 3 languages : Arabi; English; French
Title on title page
Keywords: Construction -- Libya river; River -- Libya